Law conflict in the formation of international contract - العبودي, عباس زبون; الانباري, ليث عبد الرزاق (Journal of Legal Sciences, 2019)
The present of a foreign element in the Contract will call the conflict of many laws on the conclude of the contract; usually such conflict will end to the jurisdiction of one law, but in this case it will end to the jurisdiction of many laws on the conclude of the international contract but without being a common jurisdiction, each of the conflicting law will have its own jurisdiction.